Increasing class one fruit in 'Granny Smith' and 'Cripps' Pink' apple - Fouche, Jacques Roux (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MscAgric (Horticulture))--University of Stellenbosch, 2009.